Evaluation the Effectiveness of Phenolic Compound of Salvia Frigida on Induced Atopic Dermatitis in Experimental Mice - Zahra Hassan; Tuka Hassan; Ahmed Abu-Rghif (College of Pharmacy University of Baghdad, 2022)
Abstract To evaluate the effectiveness of Phenolic Compound of Salvia Frigida on induced atopic dermatitis (AD) of mice. Forty mice were included in the study, divided in to four groups (10 mice/group): apparently healthy, induced AD without treatment, induced AD treated with tacrolimus 0.1% ointment, and induced AD treated with Phenolic Compound of Salvia Frigida cream 5%. Examination of histopathology was done and skin homogenates levels also measured. Levels of WBC, Eosinophil, skin tissue homogenate of IL-13 and IL-4, serum IgE, and histopathological scores were significantly increased among induced non treated AD group in comparison with control group. Comparisons of non-treated induced AD group with Salvia Frigida  or Tacrolimus treated groups; shows a significant reduction in the levels of all studied parameters' (WBC, Eosinophil, skin tissue homogenate of IL4- and IL-13, serum IgE, observational severity score, and histopathological scores) after the application of Tacrolimus 0.1% ointment. While after application of phenolic compound cream 5%, its shows a significant reduction in the levels of all parameters except these of (eosinophil, IgE, and IL-13). Comparison between the effect of topical application of tacrolimus and phenolic compound on the studied variables shows that the levels of epidermal thickness was significantly lower after application of phenolic compound among studied groups, while the levels of WBC and inflammatory cell were significantly lower after application of tacrolimus among studied groups. Using of these therapeutic agents that targeting IgE, IL-4 and IL-13 will probably useful in treatment of AD.